Waqf Land Management: Case Study on Waqf of Rice Field Gontor - Mulyono Jamal; Muhammad Shulthoni; Yunita Wulandari; Hendri Setiyo Wibowo (AIBPM Publisher, 2022)
This study aims to determine the waqf management in Gontor, especially in the waqf of rice fields. Pondok Modern Darussalam Gontor (PMDG) is one of the educational institutions in Indonesia that was donated in 1958. Gontor has several waqf lands that continue to grow every year. Its management is essential to know so that it can be imitated by those who need it. The Foundation of Waqf Preservation and Development of Pondok Modern Gontor (YPPWPM) manages Gontor's waqf assets in all its management. PMDG has a land area of 16.258.598 m2 or about 1.626 ha, spread throughout Indonesia. The rice fields have the most significant portion of their utilization, including the agricultural sector. This research is a descriptive study and the data comes from interviews and literature related to the waqf of Gontor. The results showed that the management of the waqf of rice fields owned by Gontor was managed by using a profit-sharing and rental system (ijarah). The waqf of rice fields in Ponorogo, Madiun, Kediri, Nganjuk, and Jember are operated by using a rental system. Whereas, waqf lands located in the Mantingan area are managed by utilizing a profit-sharing scheme. Hopefully, the study is able to enrich the literature on productive waqf land management. Keywords: Gontor, Ijarah, Profit-sharing, Waqf management, Waqf of rice field, YPPWPM.